2003
DOI: 10.1002/jbm.a.20003
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations in hydrogel chemistry control photoencapsulated chondrocyte behavior and their extracellular matrix production

Abstract: In engineering a cell-carrier to support cartilage growth, hydrogels provide a unique, largely aqueous environment for 3-dimensional chondrocyte culture that facilitates nutrient transport yet provides an elastic framework dictating tissue shape and supporting external loads. Although the gel environment is often >90% water, we demonstrate that slight variations in hydrogel chemistry control gel degradation, evolving macroscopic properties, and ultimately the secretion and distribution of extracellular matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
168
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 25 publications
5
168
0
Order By: Relevance
“…Western blot analysis of MT1-MMP indicated that its activity after 4 h post-seeding was enhanced in both PEGylated and non-modified 3-D gels as compared to 2-D culture ( Figure 3B). MT1-MMP activity in 3-D PEGylated fibrin gels was markedly increased starting from day 6 (bands 8,9,11,12) and was comparable to the activity in non-modified fibrin.…”
Section: Huvecs and Hascs Express Various Mmps And Mt-mmps When Cultumentioning
confidence: 73%
See 1 more Smart Citation
“…Western blot analysis of MT1-MMP indicated that its activity after 4 h post-seeding was enhanced in both PEGylated and non-modified 3-D gels as compared to 2-D culture ( Figure 3B). MT1-MMP activity in 3-D PEGylated fibrin gels was markedly increased starting from day 6 (bands 8,9,11,12) and was comparable to the activity in non-modified fibrin.…”
Section: Huvecs and Hascs Express Various Mmps And Mt-mmps When Cultumentioning
confidence: 73%
“…Among synthetic hydrogels, poly(ethylene glycol) (PEG) is a commonly used material for tissue engineering applications. PEG offers a mechanically stable, biocompatible 3-D platform in which living cells can be encapsulated and cultured in vitro or implanted in vivo [12]. Many protocols exist for the modification of PEGs with different chemical functional groups; for example, PEG can be conjugated with peptides, enzymes, proteins, and other biomaterials for use in tissue engineering and drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that the degradation rate of gels encapsulating chondrocytes can regulate their ability to form cartilage-like tissues in vitro. [14] However, the data provided in this manuscript is the first demonstration of this relationship in vivo. It is also possible that host cells migrated into the rapidly degrading gels more effectively, and participated in the tissue formation coupled with the transplanted chondrocytes.…”
mentioning
confidence: 78%
“…In some applications, such as cartilage tissue engineering, early efforts found success when focused primarily on mechanical characteristics of the scaffolds, thereby recapitulating the basic tissue properties while simultaneously supporting chondrocyte function (e.g., survival and secretory properties). (3)(4)(5) However, other tissue engineering applications necessitated the development of scaffolds that introduced biochemical signals to promote or direct desired cell function, and this led to significant advances in bioconjugation methods to tether proteins and small molecules, conferring functionalization and signaling to embedded cells. Such approaches have been exploited to design materials that preferentially differentiate stem cells into different lineages, (6,7) increase production of extracellular matrix (ECM) components, (8) direct cell migration, (9)(10)(11) and control extension of axons.…”
Section: Introductionmentioning
confidence: 99%